The "God of Israel" in history and tradition - Stahl, Michael J.; New York University (Leiden Boston Brill, 2021)
Acknowledgements -- List of Tables -- Abbreviations -- 1 The "God of Israel" in Biblical and Ancient Israelite Religion: Problems and Prospects -- 1.1 Introduction -- 1.2 Intellectual Horizons: Divine Identities in Scholarly Discourse -- 1.3 Theory and Method -- 1.4 The Data -- 1.5 The Scope of This Study -- 2 The "God of Israel" and the Politics of Divinity in Ancient Israel -- 2.1 Who was the "God of Israel"? -- 2.2 The Early Politics of God: El as "God of Israel" and Israel's Collective Political Heritage -- 2.3 The "God of Israel" in Transition: Judges 5 -- 2.4 When did YHWH Become the "God of Israel"? -- 2.5 YHWH and/or Baal? the Omrides in History and Biblical Tradition -- 2.6 The "God of Israel" between Collective and King: Conclusions -- 3 The "God of Israel": The God of Judah? -- 3.1 The Problem of the "God of Israel" in Monarchic Judah -- 3.2 Will the Real God of Judah Please Stand Up? -- 3.3 "YHWH of Hosts" and the Politics of Divinity in Monarchic Judah -- 3.4 The "God of Israel" in the Books of Kings -- 3.5 The "God of Israel" and Judah's Claim to Israel's Name -- 3.6 Kings and Priests, Palace and Temple: the "God of Israel" in Court and Cult -- 3.7 The "God of Israel" and the Politics of Late Monarchic Judah: Conclusions -- 4 The "God of Israel": The God of Yehud -- 4.1 The "God of Israel" after Kings (Ezekiel and Second Isaiah) -- 4.2 Ezra and Chronicles: Composition Histories, Dates, Settings, and Ideological Foci -- 4.3 "YHWH, God of Israel-He Is the God Who Is in Jerusalem": Ezra 1-6 -- 4.4 "YHWH, God of Israel, You Are Just": The "God of Israel" in Ezra 7-10 -- 4.5 "YHWH of Hosts, God of Israel, Is Israel's God": The "God of Israel" in Chronicles -- 4.6 The "God of Israel" and the Religious Politics of Post-Monarchic Yehud: Conclusions -- 5 The "God of Israel": The God of the Hebrew Bible -- 5.1 The "God of Israel": The God of the Hebrew Bible? -- 5.2 The "God of Israel" in Jeremiah -- 5.3 The "God of Israel" in Psalms -- 5.4 The "God of Israel" in Joshua -- 5.5 The "God of Israel" in Judges -- 5.6 The "God of Israel" in Exodus -- 5.7 The "God of Israel" in Isaiah -- 5.8 The "God of Israel": The God of the Hebrew Bible -- Bibliography -- Index.
In The "God of Israel" in History and Tradition , Michael Stahl provides a foundational study of the formulaic title "god of Israel" ( 'elohe yisra'el ) in the Hebrew Bible. Employing critical theory on social power and identity, and through close literary and historical analysis, Dr. Stahl shows how the epithet "god of Israel" evolved to serve different social and political agendas throughout the course of ancient Israel and Judah's histories. Reaching beyond the field of Biblical Studies, Dr. Stahl's treatment of the historical and ideological significances of the title "god of Israel" in the Hebrew Bible offers a fruitful case study into the larger issue of the ways in which religion may shape-and be shaped by-social and political structures
Includes bibliographical references and index
Keywords: God (Judaism); Hochschulschrift